Study of Contribution of Technical Communication towards Achieving Corporate Objectives in the Information Technology Industry - Dalvi, Meghashri (SFIMAR Research Review, 2016)
Technical communication is a field involving designing and developing communication products that transfer technical or specialized information from the experts who know it to others who need to know it. Acknowledging its key significance in the Information Technology industry, this research attempts to quantify and measure the involved variables, and then determine to what extent Technical Communication contributes towards achieving Corporate Objectives. To get a complete 360Â° view of the value of technical communication, the study focuses on all the stakeholders-Users of Technical Communication, Technical Communicators, and Corporate Managers; and brings forth extensive inferences that have strong practical applications.